# If (2 - 3i) + (x + yi) = 6, what is x + yi?

**Solution:**

Given, (2 - 3i) + (x + yi) = 6

We have to find x + yi

The equation can be rewritten as

2 - 3i + x + yi = 6 + 0i

Grouping of common terms,

x + yi = 6 + 0i - 2 + 3i

x + yi = 4 + 3i

Therefore, x + yi = 4 + 3i

Example: **If (3 - 3i) + (x + yi) = 5, what is x + yi?**

**Solution:**

Given, (3 - 3i) + (x + yi) = 5

We have to find x + yi

The equation can be rewritten as

3 - 3i + x + yi = 5 + 0i

Grouping of common terms,

x + yi = 5 + 0i - 3 + 3i

x + yi = 2 + 3i

Therefore, x + yi = 2 + 3i.

## If (2 - 3i) + (x + yi) = 6, what is x + yi?

**Summary:**

If (2 - 3i) + (x + yi) = 6, then x + yi is 4 + 3i.

Math worksheets and

visual curriculum

visual curriculum